2019
DOI: 10.1101/781914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White matter in infancy is prospectively associated with language outcome in kindergarten

Abstract: Language acquisition is of central importance to a child's development. Although the trajectory of acquisition is shaped by input and experience postnatally, the neural basis for language emerges prenatally. Thus a fundamental question remains unexamined: to what extent may the structural foundations for language established in infancy predict long-term language abilities? In this longitudinal neuroimaging investigation of children from infancy to kindergarten, we find that white matter organization in infancy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Our multiparametric analysis approach demonstrated that children aged 3.5 with a relatively more mature SLF coinciding with cortical features of the angular gyrus, thalamus, fusiform gyrus, middle temporal regions, and the dorsolateral prefrontal cortex are associated with better pre-reading skills at 4.5 years of age. Though this finding would not survive FDR correction, this association between the SLF and pre-reading measures is consistent with recent findings that the microstructure of the arcuate fasciculus (a sub-section of the SLF) during infancy is associated with phonological awareness skills (Woodcock Johnson Oral Language Assessment) and vocabulary knowledge (Peabody Picture Vocabulary Test -IV) in Kindergarten (Zuk et al, 2019). The SLF, including the arcuate fasciculus, supports communication between specific regions and networks in the brain and is related to pre-reading skills.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our multiparametric analysis approach demonstrated that children aged 3.5 with a relatively more mature SLF coinciding with cortical features of the angular gyrus, thalamus, fusiform gyrus, middle temporal regions, and the dorsolateral prefrontal cortex are associated with better pre-reading skills at 4.5 years of age. Though this finding would not survive FDR correction, this association between the SLF and pre-reading measures is consistent with recent findings that the microstructure of the arcuate fasciculus (a sub-section of the SLF) during infancy is associated with phonological awareness skills (Woodcock Johnson Oral Language Assessment) and vocabulary knowledge (Peabody Picture Vocabulary Test -IV) in Kindergarten (Zuk et al, 2019). The SLF, including the arcuate fasciculus, supports communication between specific regions and networks in the brain and is related to pre-reading skills.…”
Section: Discussionsupporting
confidence: 89%
“…Children aged 6-7 years who subsequently received a diagnosis of dyslexia had reduced cortical thickness in left hemisphere reading-related regions compared to children who did not eventually receive a diagnosis (Clark et al, 2014). While neuroimaging studies have identified isolated imaging measures associated with reading ability in school-age children, the neurobiological development underlying the development of reading skills may begin earlier in life (Zuk et al, 2019). Even before formal reading education, the development of language and pre-reading skills are supported by the developing structural and functional architecture of the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ac.uk/fsl; Basser et al, 1994;Langer et al, 2017;Smith et al, 2004;Zuk et al, 2021). Diffusion-weighted images were subsequently processed with the VISTALab mrDiffusion toolbox and diffusion MRI software suite (www.vistalab.com), which included tensor-fitting estimations with a linear least-squares (LS) fit for diffusion tensor fitting.…”
Section: Initial Quality Control Of Diffusion Images Was Then Conduct...mentioning
confidence: 99%
“…White matter pathways were quantified utilizing the Automated Fiber Quantification (AFQ) software package (https://github.com/jyeatman/ AFQ; Yeatman et al, 2012). Procedures employed follow those previously described in prior investigations with infants with the present research team (Langer et al, 2017;Zuk et al, 2021). In summary, whole-brain tractography was conducted via a deterministic streamline tracking algorithm (Basser et al, 1994;Mori et al, 1999), with an FA threshold of 0.1 and angle threshold of 40 • (in accordance with previous investigations with this age range (Langer et al, 2017;Zuk et al, 2021)).…”
Section: Automated Fiber Quantificationmentioning
confidence: 99%